Dual mechanisms of Ni and Si sludge-derived catalyst for catalytic methanation with high CO2 conversion and CH4 selectivity. Issue 2 (April 2023) - Fang, Wanyu; Liu, Xinyu; Zhang, Jia; Hou, Hao; Yue, Yang; Qian, Guangren
Abstract: Catalytic CO2 methanation is devoted to both carbon-emission reduction and valuable-product generation. Ni-based catalyst is widely investigated for its effective CO2 conversion and high CH4 selectivity. However, seldom work reported resource substitution for production of Ni-based catalyst. In this work, Ni-Si catalysts are synthesized from Ni-rich and Si-rich electroplating sludges by a simple coprecipitation method, and applied in catalytic CO2 methanation. As a result, CO2 conversion and CH4 selectivity of sludge-derived catalyst are both increased when the catalytic temperature is increased from 250 °C to 450 °C. The best catalyst converts 58.3% of CO2 together with a high CH4 selectivity of 88.6% at 450 °C. After detailed characterizations, the high performance is attributed to two mechanisms. On one hand, Ni 0 /Ni 2+ couple in NiO contributes to electron and material transfers in low-temperature CO2 methanation. On the other hand, an interface (NiSi2 ) is formed between NiO and Si in the sludge-derived catalyst. Ni 0 /Ni 2+, Si 0 /Si n+ (n = 3 and 4), and their combination in the interface play the main role in CO2 methanation at high temperature. Therefore, this work is in favor of utilizing wastes (CO2 and sludge) to produce cost-effective products (CH4 and catalyst). Graphical Abstract: ga1 Highlights: CO2 methanation catalysts are synthesized from Ni and Si sludges. Best CO2 conversion was 58.3% together with a high CH4 selectivity of 88.6%. The performance was comparable to that of pure-reagent-synthesized catalyst. Enhanced electron transfers on Ni/Si interface determined the performance. Electroplating sludges are potential resources for catalyst synthesis.